The Role of Social Media in Mastering Broiler Livestock Management - Ramdani, Muhamad Giri; Kusumastuti, Anie Eka; Akhiroh, Puji (Jurnal Ilmu Ternak Universitas Padjadjaran, 2024)
Social media has experienced rapid development and has had a significant impact on various aspects of life, including the broiler livestock industry. Social media plays an important role in increasing the practical skills needed for effective broiler livestock raising management, including playing a role in providing easy and fast access to information, education, and interaction between individuals. This research aimed to analyze the influence of social media roles as an information medium, educational medium, and networking & communication medium for mastering broiler management. The research method used a quantitative approach using a survey method. Data were collected through direct interviews using structured questionnaires with a Likert scale of 1-5, observation, and documentation. The data was then analyzed by multiple regression analysis and descriptive analysis. The results indicate that the variables of information media, educational media, and networking & communication media simultaneously significantly affect broiler management mastery. Specifically, variables of information media and networking & communication media have a significant influence on management mastery, while educational media does not. It can be concluded that social media plays a significant role in enhancing broiler management mastery, with information media being the most dominant variable. The findings of this study are expected to serve as a foundation for optimizing the use of social media in the broiler livestock industry, thereby improving the effectiveness and efficiency of management practices.